Nephrotic syndrome of minimal change disease following exposure to mercury-containing skin-lightening cream - Lin Zhang; Fuyou Liu; Youming Peng; Lin Sun; Chunguo Chen (Annals of Saudi Medicine, 2014)
A 28-year-old female suffered from nephrotic syndrome after a long-term use of mercury-containing, skin-lightening cream. The blood and urinary mercury content of this patient increased with use. Renal biopsy showed minimal change disease. Her symptoms were relieved 6 months after discontinuing use of the cream and receiving sodium dimercaptosulfonate and glucocorticosteroid treatments. Proteinuria disappeared, and blood and urinary mercury levels returned to normal. Previous reports of nephrotic syndrome caused by mercury-containing, skin-lightening creams have mostly been identified as being due to membranous nephropathy. Minimal change disease has been reported in a few case reports published in the English language. Here we report a case of nephrotic syndrome with minimal change disease following exposure to a mercury-containing, skin-lightening cream. We also reviewed relevant published reports to summarize clinical features and treatments and to explore the possible mechanisms involved.